2022
DOI: 10.1186/s12957-021-02451-8
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of Apatinib combined with TACE in the treatment of hepatocellular carcinoma: a meta-analysis

Abstract: Background The timely and effective treatments are vital to the prognosis of patients with hepatocellular carcinoma, and the role of Apatinib combined with TACE in the treatment of hepatocellular carcinoma remains unclear. Therefore, we aimed to conduct a systematic review and meta-analysis to evaluate the efficacy and safety of Apatinib combined with transcatheter arterial chemoembolization (TACE) in the treatment of hepatocellular carcinoma. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The inclusion criteria were: (1) Patients with primary non-diffuse unresectable HCC who were Barcelona Clinic Liver Cancer (BCLC) stage B/C, or those who showed recurrence following surgery; (2) Clinically or pathologically confirmed unresectable HCC with at least one measurable lesion according to the modified version of the Response Evaluation Criteria for Solid Tumors (mRECIST); (3) No systemic chemotherapy, targeted therapy other than apatinib (such as sorafenib, regorafenib), or immunotherapy other than camrelizumab (including PD-1/PD-L1/CTLA-4 inhibitors) was used; (4) aged 18-80 years old; (5) Eastern Cooperative Oncology Group Performance Status score (ECOG PS) of 0-1 within one week before treatment; (6) Less than 60% of the liver volume was occupied by tumors; (7) There are no serious comorbidities, such as hypertension, coronary heart disease, psychiatric history, or serious allergies; (8) Patients with Child-Pugh A or B (score 7), normal renal function, and normal coagulation function or be corrected after treatment; (9) Have received as least one cycle of systemic treatment (one dose of camrelizumab plus three weeks of apatinib for TACE + AC group, and three weeks of apatinib for TACE + A group). Patients received other treatment such as microwave ablation or radiofrequency ablation or changed targeted regimen before disease progression were excluded.…”
Section: Study Design and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria were: (1) Patients with primary non-diffuse unresectable HCC who were Barcelona Clinic Liver Cancer (BCLC) stage B/C, or those who showed recurrence following surgery; (2) Clinically or pathologically confirmed unresectable HCC with at least one measurable lesion according to the modified version of the Response Evaluation Criteria for Solid Tumors (mRECIST); (3) No systemic chemotherapy, targeted therapy other than apatinib (such as sorafenib, regorafenib), or immunotherapy other than camrelizumab (including PD-1/PD-L1/CTLA-4 inhibitors) was used; (4) aged 18-80 years old; (5) Eastern Cooperative Oncology Group Performance Status score (ECOG PS) of 0-1 within one week before treatment; (6) Less than 60% of the liver volume was occupied by tumors; (7) There are no serious comorbidities, such as hypertension, coronary heart disease, psychiatric history, or serious allergies; (8) Patients with Child-Pugh A or B (score 7), normal renal function, and normal coagulation function or be corrected after treatment; (9) Have received as least one cycle of systemic treatment (one dose of camrelizumab plus three weeks of apatinib for TACE + AC group, and three weeks of apatinib for TACE + A group). Patients received other treatment such as microwave ablation or radiofrequency ablation or changed targeted regimen before disease progression were excluded.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…It is noteworthy that 27.5% of patients in the 750 mg cohort and 40% in the 850 mg cohort had previously undergone locoregional therapies [ 6 ]. Furthermore, a meta-analysis involving 14 randomized controlled trials has demonstrated that apatinib plus TACE is more effective than TACE alone for patients with unresectable HCC [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that TACE combined with sorafenib can significantly prolong PFS in patients with advanced HCC, [6,7] and TACE combined with apatinib can significantly improve the survival outcome of HCC patients compared with TACE alone. [35] In the setting of combined TACE treatment, apatinib and sorafenib can benefit patients with advanced HCC, but their efficacy and safety are still controversial in clinical studies directly comparing apatinib plus TACE and sorafenib plus TACE. [10,11] Based on this, we conducted a comprehensive literature search (up to August 14, 2023) to evaluate the efficacy and safety of a new TKI (apatinib) versus a traditional TKI (sorafenib) in the first-line treatment of advanced HCC, including evaluating the differences in efficacy and safety of these 2 TKIs in the setting of combined TACE treatment, so as to provide evidence for clinical rational drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Although a relevant study has shown that T-T combination therapy has a positive effect on patients with advanced HCC ( 55 ), it is still weaker than triple therapy with T-T-C. The reasons can be summarized as follows: TACE can cause local necrosis of tumors, cause tumor tissues to release antigens, trigger anticancer immune responses, increase the expression of PD-1 and improve tumor recognition ability.…”
Section: Discussionmentioning
confidence: 99%